Three New Compounds from Delphinium kamaonense Hunth and Their in Vitro Cytotoxic and Potential Antioxidant Activities. Issue 7 (4th July 2022) - Gong, Chang; Zhou, Guangxin; Jing, Di; Song, Huijie; Xu, Jixuan; Meng, Dali
Abstract: A new amide (1 ), two new phenylpropanoid derivatives (2, 3 ), along with three new natural products, including three nitrogen chirality compounds, N ‐(3‐methoxy‐1, 3‐dioxopropyl)‐D‐phenylalanine methyl ester (4 ), N ‐(3‐methoxy‐1, 3‐dioxopropyl)‐L‐phenylalanine methyl ester (5 ), and N ‐acetyl‐L‐phenylalanine methyl ester (6 ), as well as dimethyl (2 R, 3 R )‐2‐hydroxy‐3‐((( E )‐3‐(4‐hydroxyphenyl)acryloyl)oxy)succinate (7 ) and dimethyl ( S, E )‐2‐((3‐(4‐hydroxy‐3‐methoxyphenyl)acryloyl)oxy)succinate (8 ) were isolated from Delphinium kamaonense Hunth. Their structures were elucidated by extensive analysis of 1D and 2D NMR, and HR‐ESI‐MS experiments, and the absolute configurations were determined by comparative analysis of specific optical rotation. Compound 1 exhibited a moderate cytotoxicity effect against Hep‐3B cancer cell lines (IC50 41.39±0.13 μM) and an excellent antioxidant activity (IC50 0.527±0.06 μM in ABTS assay, and 1.235±0.09 μM in DPPH assay, respectively), which was superior to vitamin C in ABTS (IC50 1.670±0.07 μM) and DPPH (IC50 19.10±0.40 μM) methods. Abstract :